Mathematical modeling of the kinetics of multiple ethanol intake - G. V. Nedugov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The aim of the study is to construct a mathematical model of the kinetics of multiple ethanol intake based on the kinetic equation of zero-order ethanol elimination with absorption and irrevocable first-order absorption deficiency, as well as its implementation in the format of a computer program. Analytical mathematical modeling of the kinetics of multiple oral administration of ethanol is performed on the basis of this kinetic equation. In the course of modeling, a kinetic summation method was developed that allows to perform a mathematical description of the dynamics of ethanol content in the body in the case of repeated intake of alcoholic beverages of any volume and strength, separated by time intervals of any duration. The developed computational algorithm is implemented in the format of the Alcohol Calculator V 3.0 computer program. The conclusion is made about the expediency of using the developed information and computing technology in the forensic assessment of the quantitative alcohol content in the body at a legally relevant time.